Structural diversity and photocatalytic properties of Cd(ii) coordination polymers constructed by a flexible V-shaped bipyridyl benzene ligand and dicarboxylate derivatives. Issue 4 (1st December 2014) - Liu, Lei-Lei; Yu, Cai-Xia; Ma, Feng-Ji; Li, Ya-Ru; Han, Jing-Jing; Lin, Lu; Ma, Lu-Fang
Abstract : Reactions of Cd(OAc)2 with V-shaped bipyridyl benzene and five benzenedicarboxylic acid derivatives gave rise to five new CPs. Complexes1–5 exhibited relatively good photocatalytic activity towards the degradation of methylene blue. Abstract : Hydrothermal reactions of Cd(OAc)2 ·2H2 O with a flexible V-shaped bipyridyl benzene ligand and five benzenedicarboxylic acid derivatives gave rise to five new coordination polymers i.e., [Cd(1, 4-BDC)(bpmb)(H2 O)] n (1 ), {[Cd(1, 3-BDC)(bpmb)]·0.125H2 O} n (2 ), [Cd2 (5-Me-1, 3-BDC)2 (bpmb)2 ] n (3 ), [Cd(5-NO2 -1, 3-BDC)(bpmb)(H2 O)] n (4 ) and [Cd(5-OH-1, 3-BDC)(bpmb)(H2 O)] n (5 ) (bpmb = 1, 3-bis(pyridine-3-ylmethoxy)benzene, 1, 4-H2 BDC = 1, 4-benzenedicarboxylic acid, 1, 3-H2 BDC = 1, 3-benzenedicarboxylic acid, 5-Me-1, 3-H2 BDC = 5-methyl-1, 3-benzenedicarboxylic acid, 5-NO2 -1, 3-H2 BDC = 5-nitro-1, 3-benzenedicarboxylic acid, 5-OH-1, 3-H2 BDC = 5-hydroxy-1, 3-benzenedicarboxylic acid). Their structures have been determined by single-crystal X-ray diffraction analyses, elemental analyses, IR spectra, powder X-ray diffraction (PXRD) and thermogravimetric analyses (TGA). Compound1 is a two-fold interpenetrating network showing the coexistence of polyrotaxane and polycatenane characters. Compounds2 and3 exhibit similar 2D (3, 5)-connected (4 2 ·6 7 ·8)(4 2 ·6) nets in which the bpmb ligands work as lockers in interlocking 1D [Cd(1, 3-BDC/5-Me-1, 3-BDC)] n chains. Compound4 shows a 2D 4-connected (6 6 ) sandwich-like structure with differently oriented [Cd(5-NO2 -1, 3-BDC)] n chains. Compound5 is a 3D supramolecular pcu net based on a 1D ladder-shaped chain. These results suggest that the substituted positions of carboxylate groups and changes in substituted R groups in the 5-position of BDC ligands have significant effect on the final structures. These compounds exhibited relatively good photocatalytic activity towards the degradation of methylene blue (MB) in aqueous solution under UV irradiation. Moreover, solid-state photoluminescence properties of1–5 were also investigated.